2019
DOI: 10.1177/1071100719868721
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Motion and Offloading in Short Leg Cast and Low and High Fracture Boots

Abstract: Background: Short leg casts (SLCs) and fracture boots are used to treat foot and ankle injuries, but the decision to use one device over the other is often subjective. This study compared the impact of SLCs and low and high fracture boots on ankle motion and offloading. Methods: Twenty healthy adults were prospectively studied. High-speed dynamic radiography was utilized to determine tibiotalar range of motion in the sagittal plane during nonweightbearing (NWB) and weightbearing (WB) gait in a shoe (control), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The smaller ankle excursion observed in the walking boot (13°) may limit or reduce muscle activity and possibly contribute to muscle atrophy in the gastrocnemius, soleus, and peroneal muscles (25–28). Nahm et al (41) observed that participants experienced between 3° and 8° of sagittal tibiotalar motion while wearing the different walking boot conditions compared with a regular shoe. Zhang et al (42) observed between 5° and 7° of sagittal ankle excursion in individuals wearing short-leg walking boots during walking.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller ankle excursion observed in the walking boot (13°) may limit or reduce muscle activity and possibly contribute to muscle atrophy in the gastrocnemius, soleus, and peroneal muscles (25–28). Nahm et al (41) observed that participants experienced between 3° and 8° of sagittal tibiotalar motion while wearing the different walking boot conditions compared with a regular shoe. Zhang et al (42) observed between 5° and 7° of sagittal ankle excursion in individuals wearing short-leg walking boots during walking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews in the area have found that NRKHDs reduce more PP than other offloading treatments by incorporating more key mechanical features, such as customized insoles/foot-device interfaces, rocker-bottom soles, controlled ankle motion, and higher cast walls/struts preferably extending up to the knee. 20 These features typically also reduce foot and ankle joint movements [21][22][23] and subsequent horizontal shear forces by using the contact surfaces as loadbearing surfaces. 24 In addition, restricted ankle movement will necessitate strategies of reducing mobility and/or increasing requirements on the contralateral limb.…”
Section: Reduction Of Pp and Shear Stress At The Dfumentioning
confidence: 99%